2001
DOI: 10.1111/j.1945-5100.2001.tb01832.x
|View full text |Cite
|
Sign up to set email alerts
|

Beryllium‐boron and aluminum‐magnesium chronology of calcium‐aluminum‐rich inclusions in CV chondrites

Abstract: Abstract-We have made Be-B measurements in six calcium-aluminum-rich inclusions (CAIs) (mostly type B inclusions) from CV chondrites and compared them to A1-Mg measurements. All CAIs show 1OB excesses in melilite that are correlated with B e B ratios. The initial *oBe/gBe ratio inferred from the correlation line is 6.2 x 10-4. In contrast to the Be-B system in melilite, the A1-Mg system in anorthite is disturbed. This is probably due to B diffusion in melilite being slow compared with Mg diffusion in anorthite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
49
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 19 publications
8
49
1
1
Order By: Relevance
“…Recently Wadhwa et al (2009) reported a small 26 Al/ 27 Al ratio of (3.20 ± 0.35) × 10 -5 in diopside-meliliteplagioclase grains in the E60-CAI, which is consistent with the value of (3.11 ± 0.33) × 10 -5 of the same CAI (Goswami et al, 1994). Consequently, the Al-Mg systematics of anorthite and melilite in the Efremovka CAIs is complicated probably because of the partial reequilibration and disturbance to various degrees (Sugiura et al, 2001).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Recently Wadhwa et al (2009) reported a small 26 Al/ 27 Al ratio of (3.20 ± 0.35) × 10 -5 in diopside-meliliteplagioclase grains in the E60-CAI, which is consistent with the value of (3.11 ± 0.33) × 10 -5 of the same CAI (Goswami et al, 1994). Consequently, the Al-Mg systematics of anorthite and melilite in the Efremovka CAIs is complicated probably because of the partial reequilibration and disturbance to various degrees (Sugiura et al, 2001).…”
supporting
confidence: 75%
“…However, there is clear evidence that some CAIs in Efremovka are disturbed for Al-Mg system, and therefore, some chondrules also could be disturbed. One Efremovka CAI shows a canonical value (Amelin et al, 2002), although others indicate disturbed (Sugiura et al, 2001) or younger (Wadhwa et al, 2009) ages. It is unlikely that the variation in CAI ages is due to prolonged duration of the CAI formation, because unaltered whole rock samples of Allende CAIs show a well-defined isochron consistent with internal mineral isochrons from these CAIs (Jacobsen et al, 2008).…”
Section: Grain Size Of Plagioclase and Possible Fe-alkali Metasomaticmentioning
confidence: 99%
See 1 more Smart Citation
“…The inferred 10 Be/ 9 Be ratios range from (3-4) × 10 −4 up to 18 × 10 −4 , albeit with significant analytical errors in most cases (McKeegan et al 2000;Sugiura et al 2001;Marhas et al 2002;MacPherson et al 2003). Among 26 Al-bearing ( 26 Al/ 27 Al ∼ 5 × 10 −5 ) CV-chondrite Ca-Alrich inclusions (CAIs), the best-constrained initial 10 Be/ 9 Be = (8.8 ± 0.6) × 10 −4 (2σ ) was reported by Chaussidon et al (2006a).…”
Section: Introductionmentioning
confidence: 99%
“…If one aims to quantitatively understand the spatial distribution of 10 Be in a certain time period, examination of different objects that formed closely in time is needed. The available CAI 10 Be data appear to show some heterogeneity, but there are large analytical uncertainties (e.g., McKeegan et al 2000;Sugiura et al 2001;MacPherson et al 2003). CM-chondrite SpinelHIBonite spherules (SHIBs) would be a good alternative target for investigating 10 Be heterogeneity, as their inferred 26 Al/ 27 Al ratios indicate that they probably formed ∼1 × 10 5 years after CAIs from surface cracks and the lack of uniform areas in these objects that are large enough to contain a typical ion microprobe spot (∼30-50 μm; e.g., ).…”
Section: Introductionmentioning
confidence: 99%